G190(P) Reliability of the Patient Reported Experience Measures Survey (PREMS) in the National Paediatric Diabetes Audit (NPDA). (27th April 2016) - Mohamed, Z; Basu, M; Randell, T; Sachdev, P; Denvir, L
Abstract : Introduction: Accurate information from service users helps in the development and improvement of service provision. Inaccurate or misleading information can be unhelpful and damaging. There is a standardised PREMS, which forms part of the yearly NPDA. Results are in the public domain. Aim: To determine how accurately the current PREMS reflected the views of the families attending a tertiary children's hospital. Methods: Families waiting to be seen were asked to fill in an electronic PREMS (August to October 2015). The process was facilitated by a medical student. There were 25 quantitative questions, identical to the standard PREMS used for parents/carers' responses. Written free text explanations for each answer and verbal feedback from the families to the facilitator were collated. Results: 75 questionnaires were completed. The responses accurately represented the families' views, except in 5 questions, where feedback revealed that the questions were ambiguous and/or that there was not an appropriate answer to choose from, eg: 1) 13% thought "waiting time" meant the time between arrival at the clinic to being seen by the doctor, rather than by any member of the diabetes team. 2) There was no option for the families to state "not applicable", when they felt that the question was not relevant to them, eg: a) 55% responded "no" to "rate whether psychological services gave you enough time to discuss your questions and concerns, " when they had not felt the need to have additional psychological support services b) 5% responded "no" to "our religious and/or cultural beliefs were respected, " when they felt that this question was not relevant to them. c) 57% responded "no" to "were you offered an interpreter", when they did not need an interpreter. d) 89% families, who were not using insulin pumps, responded "disagree", when asked if they had received sufficient information regarding pump technology, because they thought this question was not relevant to them. Conclusion: We found that some of the PREMS questions were open to misinterpretation by the families or did not have an appropriate response option available. To improve accuracy and reliability of information gained we would suggest revisions could be made to these questions.